The Role of Teachers in Teaching and Learning from Home Through TVRI Broadcasts and Whatsapp Groups: Peran Guru Dalam Kegiatan Belajar Mengajar dari Rumah Melalui Siaran TVRI dan Whatsapp Group - Auliana Fitri Yani; Enik Setiyawati (Academia Open, 2022)
This research is motivated by the Covid-19 pandemic. With the Covid-19 pandemic, all educational arrangements have changed. The educational system has undergone changes in accordance with the direction of the Government, namely implementing Distance Learning). This distance learning is carried out to break the chain of transmission of the covid-19 virus. SDN Durungbanjar Candi has a policy for different teaching and learning activities at each grade level. The research was conducted in grades 1 to 6 of SDN Durungbanjar Candi. Class 1 to 3 the learning process through TVRI broadcasts. The use of TVRI broadcasts in learning is considered easy to apply to lower classes who are not trusted to have their own cellphones or are still under full supervision by parents. In grades 4 to 6 the learning process is through the whatsapp grub application. The use of the whatsapp grub application is considered easy to implement and easy to convey communication. The research instruments used were interviews and documentation. The data collection technique used was in-depth interviews with several summons and documentation (Triangulation of Resources). Data analysis techniques are data reduction, data presentation, verification and conclusion. The role of teachers in teaching and learning activities from home starts from planning, implementing, and assessing learning. The three indicators were achieved well except during class discussions through Whatsapp Groups, this was because gathering all students to go online together and discussing was still difficult. The obstacles experienced by teachers in implementing activities from home include the presence of underprivileged students so that they do not have their own cellphones, this makes it difficult for students to accept learning from teachers, students do not have internet quotas and there are students who cannot understand the learning videos that have been given by the teacher.